Sunday Times (9 May 1926) - Brentford, William Joynson-Hicks, Viscount, 1865-1932 ; Gosse, Edmund, 1849-1928 ; O'Connor, T. P. (Thomas Power), 1848-1929 ; Cox, Harold ; Horne, Robert Stevenson, Sir, 1871-1940 ; Barrett, R. J.
9 May 1926